Audit of Antibiotic Prescription in Suspected Neonatal Sepsis at an Indian Tertiary Care Hospital - Geetha S; Deepa Patil; Raghu Prasada M S; Sathisha Aithal (Pharmacology and Clinical Pharmacy Research, 2022)
Neonatal sepsis is one of the most typical causes of neonatal morbidity and mortality in the developing world. Rational use of antibacterial is a priority to prevent the emergence of resistance and to reduce the burden of treatment failure. This study was a prospective, cross-sectional study that collected data from 148 records of clinically suspected neonatal sepsis in a tertiary care hospital between January to December 2017. The isolated organisms, prescribing patterns, approval status, and list of antibacterial in WHO Essential Medicines List/NLEM were analyzed and presented as percentages, mean and standard deviations using appropriate tables and graphs. Of the 430 antibacterials examined, single-drug formulations were most commonly prescribed [400(93.02%)]; 298(69.30%) and 427(99.30%) were approved by DCGI and USFDA, respectively; 275(63.95%) antibacterials were included in both WHO and NLEM. The most common isolated organisms were gram-negative (64.1%). The most common class of antibacterial prescribed was beta-lactams (ATC class: J01D and J01C) [251(58.37%)] followed by aminoglycosides (ATC class: J01G) [124(28.84%)] irrespective of culture and sensitivity and their generic names prescribed almost 50% (216) of drugs. Regarding outcome, 87.16% of cases recovered well. In conclusion, the rationality of antibacterial drug usage in suspected cases of neonatal sepsis was followed the majority of times, leading to better patient care and outcome.